EP-581 Prophylactic onlay mesh at emergency laparotomy: Promising early outcomes with long-acting synthetic resorbable mesh. (9th August 2022) - Alsaadi, Daniah; Stephens, Ian; Simmons, Lydia O; Bucholc, Magda; Sugrue, Michael
Abstract: Background: Careful surgical strategy is paramount in balancing the prevention of fascial dehiscence, incisional hernia (IH) and fear of additional mesh-related wound complications post-laparotomy. This study aims to review early outcomes of patients undergoing an emergency laparotomy with prophylactic long-acting resorbable synthetic TIGR® mesh, used to reduce early fascial dehiscence and potential subsequent IH. Methods: A retrospective, ethically approved review of 24 consecutive patients undergoing prophylactic TIGR® mesh placement during emergency laparotomies by a single surgeon between January 2017 and June 2021 at a University Hospital. A standardised approach included onlay positioning of the mesh, small-bite fascial closure, and a wound bundle. We recorded patient demographics, operative indications, findings, degree of peritonitis, postoperative complications, and mortality. Results: The study included 24 patients; 16/24 (66.6%) were female and mean age was 66.5 (range 31–86); 14/24 patients were ASA grade III or greater; 4/24 patients (16.6%) developed six complications and 3/6 occurred in a single patient. Complications included subphrenic abscess, seroma, intrabdominal hematoma, enterocutaneous fistula leading to deep wound infection and small bowel perforation. Five (20.8%) patients died in hospital; central venous catheter sepsis (n=1), fungal septicaemia (n=1) and multiorgan failure (n=3). Surgical site infection and seroma rates were low, occurring in 2/24 patients (4% each). Conclusions: This small study has identified that prophylactic onlay mesh in patients undergoing an emergency laparotomy is not associated with significant wound infection or seroma when used with an active wound bundle. The wider use of TIGR® to prevent fascial dehiscence and potential long-term IH prevention should be considered.